Identification and in silico structural and functional analysis of a trypsin-like protease from shrimpMacrobrachium carcinus - Viader Salvadó, José María; Aguilar Briseño, José Alberto; Gallegos López, Juan A.; Fuentes Garibay, José A.; Alvarez González, Carlos Alfonso; Guerrero Olazarán, Martha (PeerJ, 2020)
Macrobrachium carcinus (Linnaeus, 1758) is a species of freshwater shrimp widely distributed from Florida southwards to southern Brazil, including southeast of Mexico. In the present work, we identified a putative trypsin-like protease cDNA fragment of 736 nucleotides from M. carcinus hepatopancreas tissue by the 3′RACE technique and compared the deduced amino acid sequence to other trypsin-related proteases to describe its structure and function relationship. The bioinformatics analyses showed that the deduced amino acid sequence likely corresponds to a trypsin-like protease closely related to brachyurins, which comprise a subset of serine proteases with collagenolytic activity found in crabs and other crustacea. The M. carcinus trypsin-like protease sequence showed a global sequence identity of 94% with an unpublished trypsin from Macrobrachium rosenbergii (GenBank accession no. AMQ98968), and only 57% with Penaeus vannamei trypsin (GenBank accession no. CAA60129). A detailed analysis of the amino acid sequence revealed specific differences with crustacean trypsins, such as the sequence motif at the beginning of the mature protein, activation mechanism of the corresponding zymogen, amino acid residues of the catalytic triad and residues responsible for substrate specificity.